Pengembangan Media Digital Interaktif Berbasis Animasi Sebagai Sumber Belajar Alat-Alat Transportasi Untuk Sekolah Dasar - Irgi Frianda; Josua Ronaldi; Nishi Tessalonika; Risma Lailan; Salman Alfarisi; Siti Aisyah (LPPM STIKOM Tunas Bangsa, 2021)
The development of important means of transportation is taught from an early age, because at that age they have a very high curiosity, so that the delivery of information to elementary school children must be packaged in an attractive and easy to understand manner. Along with the development of technology, animation can be used as a medium of learning which is expected to improve the quality and learning interest of elementary school children. The purposes of this study are to 1) determine the effectiveness of developing animation-based interactive digital media for elementary school children 2) Knowing elementary school children's learning interest in learning animation 3) Testing the feasibility of animation-based interactive digital learning media. The development of this animation-based interactive digital media includes several stages, including the concept, data collection, design and testing of the learning animation.